Perilaku Bulling Pada Siswa Sekolah Menengah Pertama - Alini, Dela; Khairunnisa, Khairunnisa; Rika, Rika; Ansaria, Naila; Siregar, Syifa Habibah; Siregar, Ummu Habibah; Yuris, Evicenna (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to describe and analyze bullying behavior that occurs within the school environment, particularly at the junior high school level (SMP), focusing on the forms of bullying, its causal factors, and its impact on the students involved, both perpetrators and victims. The research adopts a qualitative case study method, employing data collection techniques such as direct observation, in-depth interviews, and documentation at a public school. The findings reveal that bullying manifests in physical forms (hitting, kicking), verbal abuse (mockery, insults), and psychological harm (exclusion, intimidation). Contributing factors include dysfunctional family environments, peer pressure, and weak supervision from the school. The impacts are significant, ranging from emotional disturbances and decreased learning motivation to poor academic performance and social withdrawal. This study recommends the importance of active collaboration among teachers, parents, and schools in preventing and addressing bullying comprehensively, as well as in creating a safe, inclusive, and supportive school climate for students’ holistic development.